Implementing Self-created Media in Online Teaching by English Pre-service Teacher of English Language Education at Mulawarman University - Widia Anggraeny Suharno (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2022)
English pre-service teachers at Mulawarman University had to implement instructional media in online teaching practice. As a result, the researcher was keen on researching the pre-service teacher's experience, difficulties, and the way the-preservice teacher overcame the difficulties in implementing self-created media in online teaching practice. The purposes of this study were (1) To explore the way English pre-service teacher implemented self-created media in online teaching practice; (2) To know difficulties faced by English pre-service teacher in online teaching practice; (3) To examine the way English pre-service teacher overcame the difficulties in online teaching practice. The design of the study was a qualitative research approach. The research participant was the seventh semester of English pre-service teacher at Mulawarman University. In collecting data, the researcher used interview, document, and observation. In analyzing the data, the researcher used Miles, Huberman, & Saldaña’s flow model of analysis that consists of data collection, data condensation, data display, and conclusion drawing and verification. This study showed that the pre-service teacher had to design the lesson plan, design the instructional video, use Google Meet as the platform for synchronous meeting, and implement the lesson plan in online teaching, which included pre-teaching, whilst-teaching, and post-teaching. The difficulties were related to a technical problem and a pedagogical problem. To overcome the difficulties, the pre-service teacher summarized the material during the online meeting and gave it to the students who could not join the class.